Dispersion in Options Investors’ Versus Analysts’ Expectations: Predictive Inference for Stock Returns - Andreou, Panayiotis; Kagkadis, Anastasios; Maio, Paulo; Philip, Dennis (My University, 2021)
We create a market-wide measure of dispersion in options investors' expectations by aggregating across all stocks the dispersion in trading volume across moneynesses (DISP). DISP exhibits strong negative predictive power for future market returns and its information content is not subsumed by several alternative equity premium predictors. Consistent with the implications of theoretical models that link dispersion to overpricing, the predictive power of DISP is particularly pronounced in relatively optimistic periods. Although an aggregate analysts' forecasts dispersion (AFD) measure also performs well in optimistic periods, it delivers insignificant overall predictability. This is because in the aftermath of the 2008 financial crisis, AFD was heavily driven by pessimistic forecasts and hence its increase did not reflect a true overpricing. As a result, AFD does not appear to be a robust equity premium predictor in recent years.
Keywords: Short Selling; Short-sale Constraints; Options Markets